Interaction of bovine viral diarrhea virus with bovine cumulus–oocyte complex during IVM: Detection in permissive cells - González Altamiranda, Erika Analía (2016)
Structural changes in the zona pellucida (ZP) of bovine oocytes seem to modulate their interaction with various viral agents, facilitating the viral infection in in vitro production systems. To evaluate the susceptibility of bovine oocytes to noncytopathogenic bovine viral diarrhea virus (ncp-BVDV), cumulus–oocyte complexes were exposed to 107 ​tissue culture-infective doses (TCID50)/mL of an ncp-BVDV strain during IVM (in vitro maturation). After that, cumulus cells and the ZP were removed by hyaluronidase and pronase treatment, respectively, and the percentages of oocytes with polar body were analyzed as a sign of nuclear maturation. After passage through cell culture, the virus was isolated from granulosa cells, ZP-free mature oocytes, and ZP-intact mature oocytes. These results were confirmed by reverse transcription–polymerase chain reaction. After consecutive washes, the virus remained associated with ZP-free oocytes, maintaining its replication and infectivity in permissive cells. Based on these findings, it is concluded that the classical viral isolation procedure has a predictive value to detect BVDV associated with ZP-free oocytes and that it was novelty demonstrated that both washing and trypsin treatment of oocytes were ineffective to remove BVDV infection.